Metal-promoted Mo6S8 clusters: a platform for probing ensemble effects on the electrochemical conversion of CO2 and CO to methanol. Issue 1 (4th September 2019) - Perryman, Joseph T.; Ortiz-Rodríguez, Jessica C.; Jude, Joshua W.; Hyler, Forrest P.; Davis, Ryan C.; Mehta, Apurva; Kulkarni, Ambarish R.; Patridge, Christopher J.; Velázquez, Jesús M.
Abstract : Presented herein is an investigation of a promising ternary metal sulfide catalyst that is capable of electrochemically converting CO2 to liquid and gas fuels such as methanol and hydrogen. Abstract : Presented herein is an investigation of a promising ternary metal sulfide catalyst that is capable of electrochemically converting CO2 to liquid and gas fuels such as methanol and hydrogen. When promoted by copper, an extended structure of Chevrel-phase Mo6 S8 clusters is capable of reducing CO2 and CO to methanol in aqueous conditions with an overpotential of −0.4 V vs. RHE. H2 gas is simultaneously and preferentially evolved during this process, contributing to total current densities as high as 35 mA cm −2 . It has been observed that Cu2 Mo6 S8 displays unique catalytic activity in terms of product selectivity, and we attribute this activity to molybdenum sulfide cluster units based on the results of structural, electronic, and electroanalytical characterization. Also discussed is the formulation of an interesting electronic structure–function correlation founded on the basis of X-ray absorption spectroscopic analyses and corroborated by the results of electroanalytical evaluation, where it has been observed that introduction of metal promoting species into the Chevrel-phase framework encourages charge transfer into cluster chalcogen sites.